'Bastard' daughters in the ivory tower: illegitimacy and the higher education experiences of the daughters of single mothers in the UK. Issue 5 (4th July 2018) - Gagnon, Jessica Dawn
ABSTRACT: Underrepresented students are often constructed through deficit discourses and blamed for 'lowering the bar' in higher education (Burke, P. J. 2012. The Right to Higher Education: Beyond Widening Participation . Abingdon: Routledge). If a student struggles, then that may be seen as proof of personal deficiencies – proof of her illegitimacy – and not of a system that is built to exclude her. This article explores notions of legitimacy within the university experiences of the daughters of single mothers who are first generation students through a thematic analysis of semi-structured interviews with and reflective writings from 26 undergraduate students in the United Kingdom. The theoretical and conceptual frameworks upon which this study is built include feminist theory, intersectionality theory, and the concept of social exclusion. The findings have implications for pedagogical practices in higher education. Changes should be made to create more equal learning environments not only for this underrepresented group, but also for other student groups who feel illegitimate in higher education.